Asymmetric and sexist polarization: political self-positioning as a moderator of the relationship between extremism and the justification of violence among adolescents - Francisco Villegas Lirola; Pilar Rodriguez Martinez; Antonio Jesus Segura Sánchez; Lucia Martinez Joya (Frontiers in Political Science, 2025)
In this paper, we present the results of a study on violent extremism and political self-positioning of adolescents in the province of Almerí (Spain). This research is based on a questionnaire conducted in secondary schools in Almerí (4) and Madrid (1) in May 2022. We tried to answer the following questions: are social extremism and the justification of violent illegal acts related? To what extent does political self-positioning moderate the relationship between extremism and the justification of violence among Alpha Generation adolescents? Does this occur in the same way for boys and girls? We proceeded to adapt and validate a scale of violent extremism. For a sample of 1,170 students aged 12–19 years, a hierarchical regression analysis was conducted for a multicategorical moderator variable. The results indicate that political polarization among adolescents does not manifest itself in the same way for those who identify with the most radical ideologies on the political spectrum. The endorsement of pro-violence attitudes is a notable phenomenon, particularly among boys who align with the political extreme right.